The Story of the Golden Horde Told by Coins (Japanese): 貨幣が語るジョチ・ウルス - Atik K. (Золотоордынское обозрение)
Research objectives: This article reviews the recent book by Yasuki Shinichiro, published in Japanese under the title of 貨幣が語るジョチ・ウルス in October 2023 by Seifudo Shoten. Research results and scientific novelty: Since there is no translation of the book at the moment, the English title, translated literally, would be “Story of the Golden Horde Told by Coins.” This review synthesizes the essence of Yasuki Shinichiro’s monograph, “The Story of the Golden Horde as Told by the Coins,” which represents a novel economic perspective on the Golden Horde. Amidst a resurgence of scholarly interest in the Mongol Empire and Golden Horde, Shinichiro’s work stands out for its focus on economic rather than historical or military aspects. Each of the ten chapters is methodically summarized, emphasizing his unique approach as an economist in examining the Golden Horde’s economic structure and influence. The review situates the book within the broader context of international literature on the Mongol Empire, highlighting its distinctiveness and the need for broader accessibility beyond the Japanese-speaking academic community. The comprehensive summary of each chapter underscores the author’s innovative approach to understanding the Golden Horde’s economic dynamics, offering a fresh perspective in the field of Mongol studies.